An Improved Understanding of the Influence of the Initiation Step on the Propylene Oxide Anionic Ring Open Polymerization - Cendejas, Gabriel; A. Flores, Cesar.; Arreguin, Felipe; Estrada, Aristeo; A. Flores, Eugenio; S. Vazquez, Flavio (Asian Journal of Chemistry, 2012)
The influence of the choice of three aliphatic and one aromatic potassium glycols as initiators on the bulk propylene oxide polymerization was investigated simultaneously by both theoretical and experimental methods. Special focus was made to elucidate the effect of the initiator on the final polypropylene oxide homopolymers polydispersity. The synthesized polymers were characterized through Fourier transform infrared and nuclear magnetic resonance. The polymer molecular weight is highly dependent on the starting initiator concentration, which was thoroughly established and systematically studied by size exclusion chromatography. Density functional theory calculations at B3LYP/-631Gd(+) level were done in order to elucidate the experimental results. Furthermore, the transition states were obtained for all system, which led to understand the different growth patterns.